Systemic control of protein synthesis through sequestration of translation and ribosome biogenesis factors during severe heat stress - Khaimov, Valeria; Grousl, Tomas; Theer, Patrick; Vainshtein, Yevhen; Gläßer, Christine; Mongis, Cyril; Kramer, Günter; Stoecklin, Georg; Knop, Michael; Mogk, Axel; Bukau, Bernd (FEBS letters, 2015)
Environmental stress causes the sequestration of proteins into insoluble deposits including cytoplasmic stress granules (SGs), containing mRNA and a variety of translation factors. Here we systematically identified proteins sequestered in Saccharomyces cerevisiae at 46 °C by a SG co-localization screen and proteomic analysis of insoluble protein fractions. We identified novel SG components including essential aminoacyl-tRNA synthetases. Moreover, we discovered nucleus-associated deposits containing ribosome biogenesis factors. Our study suggests downregulation of cytosolic protein synthesis and nuclear ribosome production at multiple levels through heat shock induced protein sequestrations.